Dialysis-related amyloidosis associated with a novel β2-microglobulin variant. (2nd January 2021) - Mizuno, Hiroki; Hoshino, Junichi; So, Masatomo; Kogure, Yuta; Fujii, Takeshi; Ubara, Yoshifumi; Takaichi, Kenmei; Nakaniwa, Tetsuko; Tanaka, Hideaki; Kurisu, Genji; Kametani, Fuyuki; Nakagawa, Mayuko; et al.
Abstract: Till date, there had been no reported case of dialysis-related amyloidosis (DRA) associated with a β2 -microglobulin variant. We report here a 41-year-old haemodialysis patient with systemic amyloidosis, exhibiting macroglossia and swelling salivary glands, uncommon clinical manifestations for DRA. Molecular analysis showed that the patient had a new variant of β2 -microglobulin (V27M). Extracted amyloid protein was predominantly composed of variant β2 -microglobulin. In vitro analysis revealed that this variant β2 -microglobulin had a strong amyloidogenic propensity, probably owing to the decreased stability caused by a bulky methionine residue. Our data clearly show that V27M variant is amyloidogenic and this mutation results in unusual clinical manifestations. To date, only one amyloidogenic β2 -microglobulin variant (D76N) has been reported in non-dialysis patients. It is noteworthy that the V27M and D76N variants show substantial differences in both clinical phenotypes and pathomechanical features. This is the first case of DRA associated with a naturally occurring β2 -microglobulin variant.